Epidemic Keratoconjunctivitis: The Current Situation and Recommendations for Prevention and Treatment - Meyer-Rüsenberg, Birthe (Deutscher Arzte Verlag, 2011)
BACKGROUND: Epidemic keratoconjunctivitis (EKC) is a highly contagious infection of the ocular surface. 316 cases were diagnosed in Germany in the first 8 months of 2010, corresponding to a 300% increase above the typical figures for recent years. This outbreak motivates us to present the current recommendations concerning EKC. METHODS: Selective literature review. RESULTS: EKC is an adenoviral infection that typically starts with a unilateral foreign body sensation and then develops, within a few hours or days, into bilateral keratoconjunctivitis with marked chemosis, epiphora, and photophobia. Visual impairment can persist for months because of subepithelial corneal infiltrates (nummuli) and irregular astigmatism. Randomized clinical trials have not shown any clear benefit in the acute phase from any of a variety of treatments, including steroids, calcineurin inhibitors, virostatic drugs and disinfecting agents. In the chronic phase, cyclosporin A eye drops can accelerate the regression of subepithelial infiltrates. Hygienic measures, including conscientious hand and surface disinfection, can lessen the spread of the disease. CONCLUSION: The first priority in the treatment of patients with definite or suspected EKC is the rigorous application of hygienic measures in medical facilities, particularly because there is still no effective drug treatment for this disease. No virostatic agent has yet been demonstrated to influence its course, either subjectively or objectively.